How to Deal with a Good Child? Prescribed Normality in Images of Children and Child-Adult Relations in Manhua Magazine, 1950-1960 - Guleva, Mariia (Journal of the European Association for Chinese Studies, 2021)
Children in propaganda serve various purposes and are aimed at different audiences. This paper looks at images of children in adult-oriented political cartoons from the 1950s magazine Manhua 漫畫 in order to establish the prescribed norms of child behaviour and child-adult interactions. This is achieved through analysing eulogising and satirical depictions of children as embodiments of prosperity and the future, as model citizens and moral authority, as well as misbehaving individuals and victims of abuse. Special attention is paid to the degrees of children’s agency, their ability to speak “for themselves” and to stand up to adults, and to the ensuing complications, e.g. the ambiguity of child-adult roles, the unclear ways for children to retain their “good nature” under bad influences, and even the whole idea of impeccably happy childhood under Chairman Mao. It is clear that children in the cartoons mostly act independently, speak up and pronounce their opinions, wishes, and judgements, and expect to be heard by adults. Therefore, children are not presented as voiceless or powerless. However, they are not given any higher position than the other social groups “exploited before the liberation” (labourers, women, ethnic minorities, etc.): their standing appears to be determined by their sense of duty and political consciousness.